2017
DOI: 10.1111/manc.12206
|View full text |Cite
|
Sign up to set email alerts
|

A Treatise on Oil Price Shocks and their Implications for the UK Financial Sector: Analysis Based on Time‐Varying Structural VAR Model

Abstract: In this paper, we examined the association among the energy sector stock, oil prices and stock market on the whole. We also considered the UK position from the net oil exporter to net oil importer and implications of the Global Financial Crises. Employing a Time‐Varying Vector Auto‐regressive framework on monthly data from January 1990 to June 2015 in which the sources of time variation were both the coefficients and variance‐covariance matrix of the innovations, this study found that historically oil price sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 104 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…The novelty of SOR unit root test is that it is nonlinear-unit root test, which accounts for sharp and smooth structural breaks in the time series. It is very important to account for the structural break as a unit root test ignores the structural break can yield the biased estimates (Nasir et al 2017). For instance, classical unit root tests such as Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) overlook the presence of nonlinearity and structural breaks in the series which may be potential cause of unit root problem.…”
Section: Sor Unit Root Test With Sharp and Smooth Breaksmentioning
confidence: 99%
“…The novelty of SOR unit root test is that it is nonlinear-unit root test, which accounts for sharp and smooth structural breaks in the time series. It is very important to account for the structural break as a unit root test ignores the structural break can yield the biased estimates (Nasir et al 2017). For instance, classical unit root tests such as Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) overlook the presence of nonlinearity and structural breaks in the series which may be potential cause of unit root problem.…”
Section: Sor Unit Root Test With Sharp and Smooth Breaksmentioning
confidence: 99%
“…Nasir et al [40] aimed to investigate the relationship between the energy sector stock, oil prices, and the stock market using a time-varying vector autoregressive model. Their findings reveal that oil price shocks have negatively affected the stock market.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Second, the irrational factors increased their importance by explaining ETF portfolios during the European debt crisis. Our work is substantially different from that of Nasir et al (2018, 2021) and Thampanya et al (2020) in that it focuses on explaining rational and irrational factors that affect the two prominent strategies: value and momentum, similar to Asness et al (2013). Asness et al (2013) show that value and momentum anomalies work in different asset classes and financial markets worldwide.…”
Section: Introductionmentioning
confidence: 93%
“…Second, it studies the goodness-of-fit of rational and irrational factors before, during and after a financial crisis. As Nasir et al (2018Nasir et al ( , 2021 reported, they analyze the influence of the domestic economic environment such as inflation, the exchange rate, interest rates and economic growth. They find that the global financial crisis is a gamechanger, and there is an intensive response during the period of financial turmoil.…”
Section: Introductionmentioning
confidence: 99%